Synthesis of Dibenzo[hi,st]ovalene and Its Amplified Spontaneous Emission in a Polystyrene Matrix - Paterno, Giuseppe M.; Chen, Qiang; Wang, Xiao-Ye; Liu, Junzhi; Motti, Silvia G.; Petrozza, Annamaria; Feng, Xinliang; Lanzani, Guglielmo; Muellen, Klaus; Narita, Akimitsu; Scotognella, Francesco (Angewandte Chemie International Edition, 2017)
A large number of graphene molecules, or large polycyclic aromatic hydrocarbons (PAHs), have been synthesized and display various optoelectronic properties. Nevertheless, their potential for application in photonics has remained largely unexplored. Herein, we describe the synthesis of a highly luminescent and stable graphene molecule, namely a substituted dibenzo[hi,st]ovalene (DBO 1), with zigzag edges and elucidate its promising optical-gain properties by means of ultrafast transient absorption spectroscopy. Upon incorporation of DBO into an inert polystyrene matrix, amplified stimulated emission can be observed with a relatively low power threshold (ca. 60 μJ cm−2), thus highlighting its high potential for lasing applications.
CRIS-Team Scopus Importer:2023-03-20
Keywords: amplified spontaneous emission; graphene molecules; stimulated emission; transient absorption; zigzag edges